A Narrative Review of the COVID-19 Infodemic and Censorship in Healthcare - Mitchell Liester; Sohaib Ashraf; Patricia Callisperis; Hector Carvallo; Shankara Chetty; Robert Enzenauer; Carlos Franco-Paredes; Raul Pineda; Panagis Polykretis; Rachel Wilkenson; Peter McCullough (Secrecy and Society)
Ideological and financial motivations have undermined science for decades. In this narrative review, we explore how organizations and governments used misinformation, disinformation, censorship, and secrecy to manage the COVID-19 pandemic. Various rationales for employing censorship and secrecy during the COVID-19 pandemic are examined including how organizations and governments create confusion about the risks associated with their products and blame avoidance to shift responsibility and to avoid accountability for their actions. Methods of censorship employed during the COVID-19 pandemic are reviewed, examples are provided, and the consequences of these actions are reviewed. Information included in this review was obtained from scientific papers, government documents, mass media articles, books, and personal accounts of physicians and scientists. We examine how the use of censorship and secrecy created a challenge for scientists, physicians, politicians, and the general public in trying to understand COVID-related topics. Finally, strategies for managing censorship and secrecy during a pandemic are presented.